Structure assembly regularities in vapour-deposited gold-fullerene mixture films - Lavrentiev, V; Motylenko, M; Barchuk, M; Schimpf, C; Lavrentieva, I; Pokorný, J; Röder, C; Vacik, J; Dejneka, A; Rafaja, D (Nanoscale advances, 2020)
Self-assembly is an attractive phenomenon that, with proper handling, can enable the production of sophisticated hybrid nanostructures with sub-nm-scale precision. The importance of this phenomenon is particularly notable in the fabrication of metal-organic nanomaterials as promising substances for spintronic devices. The exploitation of self-assembly in nanofabrication requires a comprehension of atomic processes creating hybrid nanostructures. Here, we focus on the self-assembly processes in the vapour-deposited Au x C60 mixture films, revealing the exciting quantum plasmon effects. Through a systematic characterization of the Au x C60 films carried out using structure-sensitive techniques, we have established correlations between the film nanostructure and the Au concentration, x. The analysis of these correlations designates the Au intercalation into the C60 lattice and the Au clustering as the basic processes of the nanostructure self-assembly in the mixture films, the efficiency of which strongly depends on x. The evaluation of this dependence for the Au x C60 composite nanostructures formed in a certain composition interval allows us to control the size of the Au clusters and the intercluster spacing by adjusting the Au concentration only. This study represents the self-assembled Au x C60 mixtures as quantum materials with electronic functions tuneable by the Au concentration in the depositing mixture.